In vivo study of whitening effect and stain removal ability of silica based toothpaste containing blue covarine - Carteciano, Gabrielle E.
Introduction. Consciousness of the public is increasing with regard to esthetics. According to Pontefract (2004), most people consider having bright white smiles makes a person more appealing. A lot of tooth whitening products have been developed and one of these is the use of whitening toothpastes. One of the developed whitening toothpastes contains blue covarine which whitens teeth and removes stains instantly. For this reason, this study was conducted in order to verify these claimed effects. Information gathered from this study may be used by the public for consumer purposes and the academe for further research on whitening toothpastes.